Depression, sleep problems, and perceived stress among informal caregivers in 58 low-, middle-, and high-income countries: A cross-sectional analysis of community-based surveys. (January 2018) - Koyanagi, Ai; DeVylder, Jordan E.; Stubbs, Brendon; Carvalho, André F.; Veronese, Nicola; Haro, Josep M.; Santini, Ziggi I.
Abstract: Caregiving has been associated with adverse health outcomes. However, there is a paucity of multi-country, population-based studies on mental health outcomes of caregivers especially from low- and middle-income countries (LMICs). Thus, we assessed the association of caregiving with depression, sleep problems, and perceived stress in 10 high-, 27 middle-, and 21 low-income countries. Cross-sectional community-based data of the World Health Survey including 258, 793 adults aged ≥18 years were analyzed. Multivariable logistic and linear regression analyses were conducted to explore the association of past 12-month caregiving with past 12-month DSM-IV depression, and past 30-day perceived stress [range 0 (low)-100 (high)] and severe/extreme sleep problems. Nearly 20% of the individuals were engaged in caregiving with particularly high rates observed in high-income countries (HICs) (e.g., Finland 43.3%). Across the entire sample, after adjustment for potential confounders, caregivers had a significantly higher likelihood of having depression (OR = 1.54; 95%CI = 1.37–1.73), sleep problems (OR = 1.37; 95%CI = 1.25–1.50), while their mean perceived stress score was 3.15 (95%CI = 2.46–3.84) points higher. These associations tended to be stronger in HICs. A greater number of caregiving activities was associated with a greater likelihood of depression, sleep problems, and perceived stress regardless of country income levels. In conclusion, caregiving has a negative impact on mental health worldwide with possibly greater effects in HICs. Given the growing contribution of caregivers in long-term care, interventions and policies to alleviate the mental health burden of caregivers are urgently needed to maintain sustainable and effective care practices. Highlights: Approximately one fifth of the adult population in the 58 countries studied were engaged in informal care. Caregivers were more likely to have depression, sleep problems, and higher levels of perceived stress. Interventions and policies to address the mental health burden of caregivers are indispensable.